Genomic Insights Into the Archaea Inhabiting an Australian Radioactive Legacy Site - Vázquez-Campos, Xabier; Kinsela, Andrew S.; Bligh, Mark W.; Payne, Timothy E.; Wilkins, Marc R.; Waite, T. David (Frontiers in Microbiology, 2021)
During the 1960s, small quantities of radioactive materials were co-disposed with chemical waste at the Little Forest Legacy Site (LFLS, Sydney, Australia). The microbial function and population dynamics in a waste trench during a rainfall event have been previously investigated using shotgun metagenomics. This revealed a broad abundance of candidate and potentially undescribed taxa in this iron-rich, radionuclide-contaminated environment. Here, applying genome-based metagenomic methods, we recovered 37 refined archaeal MAGs (≥50% completeness, ≤10% redundancy) from 10 different major lineages. They were, mainly, included in four DPANN lineages without standing in nomenclature (LFWA-I to IV) and ‘Candidatus Methanoperedenaceae’ (ANME-2D). While most of the presented undescribed DPANN lineages show reduced genomes with limited central metabolism typical of other DPANN, the orders under the LFWA-III lineage, ‘Ca. Gugararchaeales’, ‘Ca. Burarchaeales’ and ‘Ca. Anstonellales’, may constitute distinct orders with a more comprehensive central metabolism and anabolic capabilities within the ‘Ca. Micrarchaeota’ phylum. The new ‘Ca. Methanoperedens spp.’ MAGs, together with previously published data, suggests metal ions as the ancestral electron acceptors during the anaerobic oxidation of methane while the respiration of nitrate/nitrite via molybdopterin oxidoreductases would have been a secondary acquisition. The presence of genes for the biosynthesis of polyhydroxyalkanoates in most ‘Ca. Methanoperedens’ also appears to be a widespread characteristic of the genus for carbon accumulation. We propose 23 candidate taxa based on data analysed in this manuscript, as well as four missing taxa definitions. We present evidence of four undescribed DPANN lineages and six non-conspecific ‘Candidatus Methanoperedens’, while exploring their uniqueness, potential role in elemental cycling, and evolutionary history.